Предмет: Алгебра,
автор: darik32644kisa
решите срочно плиз (х-3)/4+(х-2)/3+(х-1)/2-х=х/12
Ответы
Автор ответа:
0
(х-3)/4+(х-2)/3+(х-1)/2-х=х/12 | *12
3(х-3) + 4(х-2) + 6(х-1) - 12х = х
3х - 9 + 4х - 8 + 6х - 6 - 12х - x = 0
Решения нет!
3(х-3) + 4(х-2) + 6(х-1) - 12х = х
3х - 9 + 4х - 8 + 6х - 6 - 12х - x = 0
Решения нет!
Похожие вопросы
Предмет: Русский язык,
автор: Nikita487694
Предмет: Русский язык,
автор: shkodina1246
Предмет: Немецкий язык,
автор: HикитaX
Предмет: Математика,
автор: lyuba20132013
Предмет: Математика,
автор: retyw